Complements and Relative Complements in Modular Soft Rough Lattice - P. Geetha; S. Subharanjani (International Journal of Mathematics And its Applications, 2017)
Soft sets and rough sets are both the mathematical tools for dealing the problems of uncertainty. Soft rough set is the connection between these two mathematical approaches to vagueness and it is the generalization of rough set with respect to the soft approximation space. E.K.R.Nagarajan et al. defined the direct product of soft lattices. The complements of soft lattice has been given by E.K.R. Nagarajan et al. [11]. The complements of rough set has been defined by Ameri et al. [1]. In this paper we first define the complements of soft rough set and also the complements and relative complements of modular soft rough lattice. We discuss some theorems related to the complements and relative complements of modular soft rough lattice with an example.